2013
DOI: 10.4236/ajibm.2013.36064
|View full text |Cite
|
Sign up to set email alerts
|

The Reaserch on Characteristics of Knowledge Workers and Their Motivating Factors: A Review and Comparison Study

Abstract: The current study surveyed major studies on the characteristics of motivating factors for knowledge workers, both in the USA and in China. Comparisons were made between studies in the two countries, and new perspectives were offered on the motivating factors for knowledge workers. Future research directions were proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…To be effective, transformational leaders need to empower their team members and provide them opportunities to develop their capabilities (Kark et al, 2003;Si and Wei, 2012). Empowering project teams is especially vital due to the increasingly dynamic and fast-paced nature of work (Tjosvold et al, 2005), especially in knowledge-driven industries such as IT (Zhan et al, 2013). This may be achieved by permeating a "climate of empowerment" within the project.…”
Section: Ijmpb 152mentioning
confidence: 99%
See 1 more Smart Citation
“…To be effective, transformational leaders need to empower their team members and provide them opportunities to develop their capabilities (Kark et al, 2003;Si and Wei, 2012). Empowering project teams is especially vital due to the increasingly dynamic and fast-paced nature of work (Tjosvold et al, 2005), especially in knowledge-driven industries such as IT (Zhan et al, 2013). This may be achieved by permeating a "climate of empowerment" within the project.…”
Section: Ijmpb 152mentioning
confidence: 99%
“…Hence, an empowerment climate enables the delegation of authority and responsibility to employees (Leach et al, 2003;Mathieu et al, 2006). Knowledge workers in particular, such as those in the IT industry, tend to prefer an environment of independence where they are empowered to make decisions (Zhan et al, 2013). Furthermore, the findings of Nauman et al (2010) indicate that empowerment climate is also important for effective virtual project management.…”
Section: Empowerment Climate As a Moderatormentioning
confidence: 99%
“…Cochran and Ferrari (2009) identify the skills for success in the knowledge economy as follows: thinking skills, communication, teamwork and leadership, continuous learning and self-direction, technology adoption and application, professionalism and ethics. The research conducted by Zhan et al (2013) posits 35 characteristics of KWs by using the common features concluded in more than 10 studies. These characteristics are independence, high level of turnover, creativity, being challenging to supervise the work processes, realising self-value, being difficult to measure the work results, knowledge capital, dimly bounds of leadership and being contemptuous of the authority, being loyal to the occupations instead of employers, individual characters (Zhan et al, 2013).…”
Section: Characteristics Of Knowledge Workersmentioning
confidence: 99%
“…The research conducted by Zhan et al (2013) posits 35 characteristics of KWs by using the common features concluded in more than 10 studies. These characteristics are independence, high level of turnover, creativity, being challenging to supervise the work processes, realising self-value, being difficult to measure the work results, knowledge capital, dimly bounds of leadership and being contemptuous of the authority, being loyal to the occupations instead of employers, individual characters (Zhan et al, 2013). The common characteristics of KWs concluded from the literature are classified in this study as communication, motivation, autonomy, possessing theoretical and practical knowledge, ability to access and use information, and intellectual ability.…”
Section: Characteristics Of Knowledge Workersmentioning
confidence: 99%
“…It also indicates their level of readiness for facing hard situations, challenging weaknesses in plans and strategies and concurring them [9]. as well as the ability to refresh their knowledge and their abilities to adapt to complex missions of various environments of works [10]. So knowledge workers, in the light of this dimension (of Challenge and Achievement), employ their precious skills and knowledge developed through experience in performing works and solving perplex and unfamiliar problems they face in environments of relational resources and accumulated knowledge [11] .…”
Section: Second: Dimensions Of Knowledge Workersmentioning
confidence: 99%